Relation of fetal heart rate signals with unassignable baseline to poor neonatal state at birth - Georgieva, A; Payne, S; Moulden, M; Redman, C (2012)
Electronic fetal heart rates (FHR) are used to monitor fetal health during labour. The paper records are visually assessed by clinicians, but automated alternatives are being developed. Interpretation, visual or computerised, depends on assigning a baseline to identify key features such as accelerations and decelerations. However, when the FHR is unstable the baseline may be unassignable, making conventional analysis unreliable. Such instability may reflect on fetal health. If true, these segments should not be discarded but quantified, for which we have developed a numerical method. In 7,568 labours, the association between unassignable baseline and umbilical arterial blood pH ≤ 7.05 at birth (evidence of poor health) was studied retrospectively. We found a consistent increase of the risk for acidaemia with longer intervals of unassignable baseline. This is detectable at the end of the first stage of labour, but stronger at the end of the second stage: in the last 30 min of labour, the odds ratios (with respect to baseline assignable throughout this period) increased from 1.99 (15 min unassignable) to 4.9 (30 min unassignable). Computerised analysis of the FHR becomes unreliable when the baseline cannot be assigned; however, this pattern is itself a pathological feature associated with acidaemia at birth. © International Federation for Medical and Biological Engineering 2012.